Cultural identity in Eugenia Kim’s The Calligrapher’s Daughter - Ng, Wen Lee; Mani, Manimangai; Wan Yahya, Wan Roselezam (SciPress Ltd, 2015)
Eugenia Kim’s The Calligrapher’s Daughter (2009) is a well-received East Asian novel about a Korean Christian, Najin’s encounter with western culture. As an aristocratic woman, she is expected to uphold Korean tradition. However, as Najin realises that she is culturally marginalised by her father and the Korean traditional society mainly due to her gender, she picks up a foreign culture introduced to her, western culture. This move is extremely significant because after Najin driven by cultural marginalisation to embrace western culture, her cultural practices are no longer the same with traditional Korean women. This important turn of the novel has not been explored by scholars extensively. Thus, this study aims to depart from the cultural marginalisation faced by Najin. Furthermore, due to the fact that cultural identity formation is highly influenced by culture, there is a need to look into the changes of Najin’s cultural identity as she incorporates western culture into her Korean traditional culture. By investigating the changes of Najin’s cultural identity throughout the novel, this study finds that Najin has transformed from a nameless girl without an identity into an independent woman with the help of western education.